Redesign of the sizing process optimization to produce warp yarn with strong weaving ability - Kartika, Wahyu; Soepardi, Apriani (OPSI, 2023)
The research focuses on optimization of the sizing process parameters for cotton warp yarn material. The sizing process is a crucial step where warp yarn is coated with a starch solution before weaving. The aim is to produce warp yarn with strong weaving ability, thereby facilitating the entire process. To achieve this, several factors are considered, namely the steam bar, and squeeze roll pressure, including machine speed. The techniques used to address this issue include Taguchi in collaboration with Grey Relational Analysis (GRA) to effectively address multi-responses. In this analysis, the larger the better characteristic was applied to S/N Ratio, indicating that the higher the GRG value, the closer it is to the desired optimum condition. Based on the calculations from S/N Ratio response table for the GRG, it can be determined that factor steam bar pressure was selected at 4 Bar, with an average S/N Ratio value of -2.935. factor squeeze roll should be set to level 10 Km/m3, as it yields an average S/N Ratio value of -2.912. Factors squeeze roll) and C (Machine Speed) were selected at levels 2 (10 Km/m3) and 1 (45 M/Min) with average values of -2.912, and -4.771, respectively.